Aplikasi Messaging Dengan Algoritma Base 64 Untuk Mengamankan Data Pesan Berbasis Web - Rekky Tinendung; Sumi Khairani; Siti Sundari (UIN Sumatera Utara, 2022)
Communication is a very important human need. Communication is needed to obtain or provide information to others. Currently, there are many services available for communicating, one of the most popular telecommunication services is Chat messenger. This research will discuss a security in sending messages with the base 64 algorithm. Base64 is an encryption algorithm that is quite unique and is very helpful in hiding messages in the form of hasting. The purpose of this research is to build a web-based chat messenger software or application that is used to facilitate real-time communication, such as sending and receiving text and image messages. The results of this research are in the form of applications or websites that can send messages by inserting the base64 algorithm. Keywords: message, algorithm, data, security